Pengembangan Knowledge Management System Untuk Mengelola Pengetahuan Personel Pada Laboratorium Pengujian Slid Seameo Biotrop - Zulkarnaen Noor Syarif; Mohammad Syafrullah; Devit Setiono; Irawan Irawan; Hendri Irawan (Universitas Budi Luhur, 2022)
Knowledge of SOPs, documents, regulations, and experience is not well documented in the SEAMEO BIOTROP SLID environment to support the process of disseminating knowledge (knowledge) between employees in the SEAMEO BIOTROP SLID environment. Personnel experience and knowledge are lost when personnel are replaced, transferred, retired, or have expired personnel. At present, knowledge and experience in daily work accumulates in each personnel and is not documented in documents and systems, so it depends on each personnel. This research uses a methodology developed by Fernandez and Sabherwal. The results of this study are at the forefront of developing the knowledge management process. The knowledge management process developed at SLID SEAMEO BIOTROP is externalization, internalization, outreach for knowledge sharing, direction, routine, combination, socialization for discovery and knowledge sharing. Features created by a knowledge management system to support the knowledge management process consist of document management, knowledge management, discussion forums, and search capabilities. The prototype knowledge management system has been tested by SLID SEAMEO BIOTROP personnel using the user acceptance testing method and overall results are included in the evaluation criteria very well at the level of 84.51%.